Ecological and Physiological Observations on Polymorphic Populations of the Toad Bufo arenarum Hensel, from Argentine - Cei, José Miguel Alfredo María (1959)
The distribution area of Bufo arenarum Hensel extends from southern Brazil southward to southern Patagonia. This toad species appears to be an ecologically very versatile form, since it occurs in a great variety of ecological niches available in its distribution regions, except for the high Cordilleras. Despite the absence of obvious natural barriers between the different populations, the latter often differ in a variety of characters, such as colors and patterns, certain reflexes, and metabolic rates. These differences seem to be correlated with environmental conditions. Particularly interesting are the differences observed between the populations of the arid deserts near Mendoza and those of San Luiz, Cordoba, and Tucuman. The following account may be regarded as an exploratory study which is needed for a more thorough analysis of the population structure of the species.